LncRNA SBF2-AS1 Facilitates Nonsmall Cell Lung Cancer Progression by Targeting miR-520a-3p. (11th April 2022) - Wang, Yi; Zou, Yanzhi; Zhang, Qingmei; Chen, Defu; Lin, Lin
Abstract : Background . Long noncoding RNA (lncRNA) SET-binding factor 2 (SBF2) antisense RNA1 (SBF2-AS1), which acts as an oncogene in various cancers, can promote tumors progression. The study aimed to explore the role and molecular mechanism of SBF2-AS1 in nonsmall cell lung cancer (NSCLC). Methods . qRT-PCR was introduced to detect SBF2-AS1 and miR-520a-3p expression in NSCLC. The effects of SBF2-AS1 and miR-520a-3p on the proliferation, migration, and invasion of NSCLC cells were assessed through cell counting kit-8 (CCK-8) and transwell assay. Furthermore, the relationship of SBF2-AS1 and miR-520a-3p was verified by the RNA immunoprecipitation (RIP) assay, dual-luciferase assay, and Spearman correlation analysis. Results . In NSCLC tissues, SBF2-AS1 was highly expressed, while miR-520a-3p expression has decreased. The overall survival of NSCLC patients with high SBF2-AS1 expression was lower. SBF2-AS1 silencing repressed the proliferation, migration, and invasion of NSCLC cells. SBF2-AS1 directly interacted with miR-520a-3p, and a negative relationship was observed between their expression levels in NSCLC tissues. More importantly, the suppression of SBF2-AS1 silencing on the proliferation, migration, and invasion in NSCLC cells was counteracted by miR-520a-3p inhibition. Conclusion . SBF2-AS1 accelerated the proliferation, migration, and invasion of NSCLC cells via mediating miR-520a-3p, thus promoting NSCLC progression.